The influence of verbal cues on drop jump landing strategies in NCAA Division I soccer players - Barker, L.; Bankers, S.; Farmer, B.; Siedlik, J.; Harry, J.; Grindstaff, T. L. (American Journal of Sports Science, 2021)
Jump testing to monitor athletic performance and development has become commonplace in the field of strength and conditioning. Verbal cues of jump tests, such as the drop jump, has significant effects on performance metrics and movement strategy. The purpose of this study was to use a force platform analysis to investigate landing depth and global flexion in the lower extremity joints at initial impact between cues to maximize jump height or minimize ground contact time. Another purpose of this study was to repeat previous investigations on the influence of cueing DVJs to maximize height or minimize ground contact time on the Reactive Strength Index (RSI). Thirty-nine Division I soccer players performed one DVJ (DVJHeight) for maximum height and another DVJ (DVJQuick) for quickness. Differences in dependent variables were analyzed by Bayesian paired samples t-tests. RSI was greatest in the DVJQuick condition (Meandiff = 0.36 ± 104 (95% HDI: .232, .492). Ground contact time was shorter with the DVJQuick (Meandiff = -0.19 ± 0.028, 95% HDI: -0.224, -0.155). Jump height was less with the DVJQuick (Meandiff = -0.033 ± 0.007, 95% HDI: -0.068,.0035). Landing depth decreased during the DVJQuick (Meandiff = -0.093 ± 0.018, 95% HDI: -0.118, -0.066). Global flexion in the lower extremities at impact decreased with a DVJQuick (Meandiff = -0.057 ± 0.025, 95% HDI: -0.084, -0.031). DVJQuick resulted in a large increase in RSI due to disproportionate decreases in ground contact time (large decrease) compared to jump height (small decrease). The increase in RSI with DVJQuick coincided with a decrease in landing depth, suggesting a stiff landing strategy and increased stretch-shortening cycle intensity.